Differential expression of cyclin E, p63, and Ki-67 in gestational trophoblastic disease and its role in diagnosis and management: A prospective case-control study - Asaranti Kar; Chandraprava Mishra; Priyadarshini Biswal; Tushar Kar; Sasmita Panda; Subhasini Naik (Wolters Kluwer Medknow Publications, 2019)
Background: Gestational trophoblastic disease (GTD) constitutes a spectrum of tumors and tumor-like conditions, characterized by proliferation of pregnancy-associated trophoblastic tissue of progressive malignant potential. It is very difficult to differentiate these complex groups of lesions basing on histomorphology alone. Immunohistochemistry (IHC) with cyclin E, P63, and Ki-67 has a definite role in the identification of different trophoblasts and entities of GTD and also in the determination of biological behavior. Aims: The aim of this study is to find the differential expression of cyclin E, p63, and Ki-67 in normal placenta, hydropic abortus (HA), and various entities of GTD. Design and Settings: A prospective case-control study conducted in a government medical college. Methods: Total 96 cases, divided into Group A (48 histologically confirmed cases of GTD) and Group B (controls comprising 8 HA and 40 normal placentas of different trimesters), were studied. The histological samples were subjected to IHC using cyclin E, Ki-67, and p63. Statistical Analysis: Results were analyzed using SPSS statistical method. Results: Among the three immunomarkers used, Cyclin E and Ki-67 show statistically significant difference (P < 0.05) when compared between GTD and control groups, but it was insignificant for p63 (P = 0.369). Strong staining intensity of cyclin E and Ki-67 is seen in complete moles, choriocarcinoma, and placental site trophoblastic tumor. Conclusion: This study was done to evaluate the role of cell cycle regulatory proteins such as cyclin E and p63 and proliferation marker Ki-67 in the detection of various trophoblasts and differential diagnosis of the lesions associated with them.